2012
DOI: 10.4102/jsava.v83i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of a canine neurofibroma

Abstract: Accurate diagnostic approaches to differentiate peripheral nerve sheet tumours from others have not been firmly established. The aim of this case report was to diagnose neurofibroma using a combination of diagnostic imaging, histopathology and immunohistochemistry, which were applied to a canine neurofibroma arising in the left mandible. The tumour was surgically excised and examined histologically. Round or spindle cells, with elongated, dense and homogenous chromatin and pale cytoplasm typical of Schwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…They are positive for S-100 protein at IHC analysis, indicating their neural origin from Schwann cells [8]. Furthermore, positivity for vimentin and CD34 are also indicative of neurofibromas [9,10]. In this case, neurofibromas were demonstrated by macroscopic, histopathological and immunohistochemical characteristics.…”
Section: Discussionmentioning
confidence: 76%
“…They are positive for S-100 protein at IHC analysis, indicating their neural origin from Schwann cells [8]. Furthermore, positivity for vimentin and CD34 are also indicative of neurofibromas [9,10]. In this case, neurofibromas were demonstrated by macroscopic, histopathological and immunohistochemical characteristics.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, these studies showed that similarities between neurofibroma in animals and humans are not restricted to microscopic features, but that they also exist in regard to tumor location and patient's age (Schoniger & Summers 2009). After publication of the report by Schoniger and Summers (2009), a real neurofibroma in the neck of a dog was described (Fattahian et al 2012). In humans, PNST are usually benign neoplasm.…”
mentioning
confidence: 99%